Chenille waterproof floor mat and production process thereof
By using antibacterial water-absorbing microspheres and modified polyester materials in Chenilli floor mats, the problems of poor waterproof performance and easy bacterial growth are solved, and good water absorption and anti-fouling performance are achieved, which improves the The convenience of floor mats and hygiene and safety.
Patent Information
- Application Number
- CN202411806894.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing Chenille floor mats have poor waterproof performance due to the use of polyester materials, and are prone to bacterial growth in humid environments, and their special structure makes cleaning difficult.
Antibacterial water-absorbing microspheres and modified polyester materials are used to organize the polyester base cloth by dipping and rolling method, and use modified polyester filaments as the decorative yarn of Chenilli yarn to form modified Chenilli yarn, combining antibacterial Complexing silver ions of water-absorbing microspheres enhance the antibacterial and anti-fouling properties of the floor mat.
It significantly improves the water absorption and anti-bacterial and anti-fouling properties of Chenille waterproof floor mats, reduces the adhesion of pollutants and bacterial growth, and improves the convenience of use and hygiene and safety.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of floor mats, in particular to a chenille waterproof floor mat and a production process thereof. Background Art
[0002] Chenille yarn is a decorative yarn that is fed vertically by clamping the core yarn twisted by the ring spindle. Under the action of the twisting force, it is spirally dispersed to form a unique appearance. Chenille yarn is mostly used as a raw material for bathroom products. Currently, polyester is commonly used to manufacture bathroom products such as chenille floor mats.
[0003] Since chenille mats are mostly made of polyester, due to the nature of polyester itself, its moisture absorption performance is poor, and it will be in a humid environment for a long time, which makes it easy for bacteria to grow on the surface of the mat. At the same time, due to the special tufting structure of chenille mats, it is very easy to hide dirt and grime during daily use, which is not conducive to cleaning and use. Summary of the Invention
[0004] The purpose of the present invention is to provide a chenille waterproof mat and a production process thereof, which solves the problem of poor waterproof performance of existing polyester chenille mats and enables the mats to have good antibacterial and antifouling capabilities.
[0005] The object of the present invention can be achieved through the following technical solution: A chenille waterproof mat is made by the following steps: Step S1: mixing antibacterial water-absorbing microspheres, polyacrylic acid, and deionized water to prepare a microsphere finishing solution, wherein the mass concentration of the antibacterial water-absorbing microspheres in the microsphere finishing solution is 5-10 g / L and the mass concentration of the polyacrylic acid is 10 g / L, and finishing the polyester base fabric by a two-immersion and two-rolling method, wherein the polyester base fabric is immersed in the microsphere finishing solution, the temperature of the two immersions is 40° C., the immersion time is 1 hour respectively, the bath ratio is 1:15, the roll-off rate is 80%, and then pre-baking is performed at 80° C. for 3 minutes and baking is performed at 120° C. for 3 minutes to obtain a modified base fabric; Step S2: adding the modified polyester to a melt spinning machine, melt spinning, and producing modified polyester filaments, which are then passed through a chenille spinning machine, using two polyester filaments as core yarns and six modified polyester filaments as decorative yarns, sandwiching the decorative yarns between the two core yarns and twisting them in a spiral shape to produce modified chenille yarn; Step S3: feeding the modified chenille yarn and the modified base fabric into a tufting loom, and then dyeing, finishing, repairing, and backing the chenille yarn to produce a waterproof chenille mat; The modified polyester is prepared by the following steps: Step A1: N-methyl-4-piperidone, phenol, and deionized water were mixed, stirred at a rate of 300-350 rpm and a temperature of 5°C under nitrogen protection, and concentrated sulfuric acid was added dropwise, and the reaction was carried out for 48 hours to obtain intermediate 1. Intermediate 1, ethylene carbonate, potassium carbonate, and N,N-dimethylformamide were mixed, and the reaction was carried out under nitrogen protection at a rate of 300-350 rpm and a temperature of 160°C for 2 hours to obtain intermediate 2; The ratio of N-methyl-4-piperidone, phenol and concentrated sulfuric acid is 0.5 mol: 1-1.2 mol: 20 mL, and the ratio of intermediate 1, ethylene carbonate and potassium carbonate is 0.5 mol: 1-1.2 mol: 4 g; During the reaction, under the action of Lewis acid, the ketone group in N-methyl-4-piperidone reacts with phenol to undergo an electrophilic substitution reaction to form a bisphenol A structure, thereby producing intermediate 1. The phenolic hydroxyl group in intermediate 1 then reacts with ethylene carbonate to form a phenoxyethanol structure, thereby producing intermediate 2. Step A2: Intermediate 2, dimethyl terephthalate, and ethylene glycol were mixed, stirred at a rate of 300-400 rpm and a temperature of 200°C, and zinc acetate and antimony trioxide were added. The mixture was reacted for 2 hours, and then the temperature was raised to 250°C while maintaining a vacuum degree of -0.099 MPa for 6-8 hours to obtain a block polyester. The ratio of intermediate 2, dimethyl terephthalate, ethylene glycol, zinc acetate and antimony trioxide is 0.05 mol: 0.1 mol: 0.32-0.35 mol: 0.05-0.08 g: 0.03-0.05 g; During the reaction, the ester group in dimethyl terephthalate undergoes an ester exchange reaction with the intermediate 2 and the hydroxyl group in ethylene glycol under the action of zinc acetate catalyst to form a hydroxyethyl ester group, which then undergoes a polycondensation reaction under the action of antimony trioxide to produce a block polyester. Step A3: The block polyester, N,N-dimethylformamide and chloroform were mixed, stirred at a stirring rate of 200-300 rpm and a temperature of 60° C., and propane sultone was added, and the mixture was reacted for 48 hours to obtain a modified polyester; The ratio of block polyester to propane sultone is 4-6 g:0.01 mol; During the reaction, propane sultone ring-opens and reacts with the tertiary amine group in N-methyl-4-piperidone in the block polyester, quaternizing the tertiary amine group and introducing a sulfonium radical to obtain a modified polyester. The antibacterial water-absorbing microspheres are prepared by the following steps: Step B1: Sorbitan laurate and cyclohexane were mixed and ultrasonically dispersed for 10 minutes. Under nitrogen protection, the stirring rate was 120-180 rpm, and the temperature was 30°C. A mixture of acrylamide, N,N-methylenebisacrylamide, ammonium persulfate and deionized water was added dropwise with stirring. The mixture was then heated to 60°C, reacted for 2-3 hours, and filtered to obtain polyacrylamide microspheres. The polyacrylamide microspheres, N,N-diisopropylethylamine and dichloromethane were mixed, stirred at a stirring rate of 200-300 rpm and the temperature was 0°C, maleic anhydride and 1-hydroxybenzotriazole were added with stirring, the mixture was heated to room temperature, and the reaction was carried out for 24 hours to obtain grafted microspheres. The dosage ratio of sorbitan laurate, cyclohexane, acrylamide, N,N-methylenebisacrylamide and ammonium persulfate is 1.5-2 g:150 mL:0.05-0.08 mol:0.05 g:0.08-0.1 g, and the dosage ratio of polyacrylamide microspheres, N,N-diisopropylethylamine, maleic anhydride and 1-hydroxybenzotriazole is 6-8 g:0.5 mL:4-5 g:0.2 g; During the reaction, a mixture of acrylamide, N,N-methylenebisacrylamide, ammonium persulfate, and deionized water was dripped into a mixture of sorbitan laurate and cyclohexane using a reversed-phase suspension method. Cross-linking polymerization occurred under the action of the crosslinker N,N-methylenebisacrylamide and the initiator ammonium persulfate, producing polyacrylamide microspheres. The amide groups in the polyacrylamide microspheres then reacted with maleic anhydride under the action of catalysts N,N-diisopropylethylamine and 1-hydroxybenzotriazole. The maleic anhydride reacted with the amino groups to form amide bonds, producing grafted microspheres. Step B2: 3-mercaptopropionic acid, 1,2-phenylenediamine and hydrochloric acid solution were mixed, and the mixture was stirred at a rate of 180-240 rpm and a temperature of 100° C. under argon protection for 48 hours to obtain intermediate a. Intermediate a, grafted microspheres, ethanol and water were mixed, and the mixture was stirred at a rate of 300-400 rpm and a temperature of 60° C. for 8-10 hours to obtain modified microspheres; The molar concentration of the hydrochloric acid solution is 4 mol / L, the amount ratio of 3-mercaptopropionic acid, 1,2-phenylenediamine and hydrochloric acid solution is 0.5-0.6 mol:0.5 mol:30-40 mL, and the amount ratio of intermediate a and grafted microspheres is 0.05 mol:6-8 g; During the reaction, the carboxyl group in 3-mercaptopropionic acid first undergoes N-acylation reaction with an amino group in 1,2-phenylenediamine. The other amino group then adds to the carbonyl group to form a ring and dehydrates to form a benzimidazole structure, thereby producing a thiol-containing intermediate a. The thiol group in the intermediate a then undergoes a click reaction with the double bond in the grafted microspheres to produce modified microspheres. Step B3: Mixing the modified microspheres, silver nitrate solution, and ethanol, stirring at a rate of 300-400 rpm at room temperature for 12 hours, and filtering to obtain antibacterial water-absorbing microspheres; The mass concentration of silver nitrate solution is 0.3 mol / L, and the ratio of modified microspheres to silver nitrate solution is 1-2 g: 30 mL; During the reaction, the benzimidazole groups in the modified microspheres coordinate and complex with the silver ions in silver nitrate to produce antibacterial water-absorbing microspheres. Beneficial effects of the invention: The invention relates to a chenille waterproof mat and a production process thereof. The base fabric used for the chenille waterproof mat is modified, that is, polyacrylic acid is used as an adhesive, and polyacrylic acid undergoes self-crosslinking during the baking process, thereby arranging antibacterial water-absorbing microspheres into the base fabric to obtain a modified base fabric. The modified polyester is prepared and modified polyester filaments are prepared using the modified polyester as a raw material, and the modified polyester filaments are used as decorative yarns of the chenille yarn, so that the chenille yarn itself has good antibacterial and antifouling properties, thereby making the chenille waterproof mat have good water absorption, antibacterial and antifouling properties; the modified polyester is obtained by an ester exchange reaction between an intermediate 2 and dimethyl terephthalate and ethylene glycol, and then quaternized and sulfur radicals are introduced. Since the modified polyester has a zwitterionic structure on the side chain, The structure is arranged in a comb-like manner, which has strong hydrophilicity. When it comes into contact with water, it will combine with water molecules to avoid contact with pollutants. The steric hindrance effect of the comb-like arrangement can also reduce the attachment of proteins, so that the modified polyester filament itself has good hydrophilic and anti-fouling properties, reducing the entry of pollutants into the decorative yarn structure of the chenille yarn. The quaternary ammonium groups generated by its quaternization also have certain antibacterial properties. The antibacterial water-absorbing microspheres are based on polyacrylamide microspheres with benzimidazole structures grafted on the surface and are obtained by coordination and complexation of benzimidazole and silver ions. Since the polyacrylamide microspheres themselves have good water absorption properties, they quickly absorb water when the chenille waterproof mat comes into contact with water, thereby playing a waterproof role. At the same time, the silver ions coordinated on its surface can play a certain antibacterial role. DETAILED DESCRIPTION
[0006] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention. Example 1
[0007] A chenille waterproof mat is made by the following steps: Step S1: mixing antibacterial water-absorbing microspheres, commercially available Mingtu Chemical 2000 molecular weight polyacrylic acid, and water to prepare a microsphere finishing solution, wherein the mass concentration of the antibacterial water-absorbing microspheres in the microsphere finishing solution is 5 g / L and the mass concentration of the polyacrylic acid is 10 g / L, and finishing is performed on a commercially available Juntong polyester base fabric using a two-immersion and two-rolling method, wherein the polyester base fabric is immersed in the microsphere finishing solution, the two immersion temperatures are 40° C., the immersion time is 1 h, the bath ratio is 1:15, the roll-off rate is 80%, and then pre-baking is performed at 80° C. for 3 min and baking is performed at 120° C. for 3 min to obtain a modified base fabric; Step S2: adding the modified polyester to a melt spinning machine, melt spinning, and producing modified polyester filaments, which are then passed through a chenille spinning machine, using two commercially available Yongxing polyester yarns as core yarns and six modified polyester filaments as decorative yarns, sandwiching the decorative yarns between the two core yarns and twisting them in a spiral shape to produce modified chenille yarn; Step S3: feeding the modified chenille yarn and the modified base fabric into a tufting loom, and then dyeing, finishing, repairing, and backing the chenille yarn to produce a waterproof chenille mat; The modified polyester is prepared by the following steps: Step A1: N-methyl-4-piperidone, phenol, and deionized water were mixed, stirred at a rate of 300-350 rpm and a temperature of 5°C under nitrogen protection, and concentrated sulfuric acid was added dropwise, and the reaction was carried out for 48 hours to obtain intermediate 1. Intermediate 1, ethylene carbonate, potassium carbonate, and N,N-dimethylformamide were mixed, and the reaction was carried out under nitrogen protection at a rate of 300-350 rpm and a temperature of 160°C for 2 hours to obtain intermediate 2; The ratio of N-methyl-4-piperidone, phenol and concentrated sulfuric acid is 0.5 mol:1 mol:20 mL, and the ratio of intermediate 1, ethylene carbonate and potassium carbonate is 0.5 mol:1 mol:4 g; Step A2: Intermediate 2, dimethyl terephthalate, and ethylene glycol were mixed, stirred at a stirring rate of 300 rpm and a temperature of 200°C, and zinc acetate and antimony trioxide were added. The mixture was reacted for 2 hours, and then the temperature was raised to 250°C while controlling the vacuum degree to -0.099 MPa and the reaction was continued for 6 hours to obtain a block polyester. The ratio of intermediate 2, dimethyl terephthalate, ethylene glycol, zinc acetate and antimony trioxide is 0.05 mol: 0.1 mol: 0.32 mol: 0.05 g: 0.03 g; Step A3: The block polyester, N,N-dimethylformamide and chloroform were mixed, stirred at a stirring rate of 200 rpm and a temperature of 60° C., and propane sultone was added, and the mixture was reacted for 48 hours to obtain a modified polyester; The ratio of block polyester to propane sultone was 4 g:0.01 mol; The antibacterial water-absorbing microspheres are prepared by the following steps: Step B1: Sorbitan laurate and cyclohexane were mixed and ultrasonically dispersed for 10 minutes. Under nitrogen protection, the stirring rate was 120 rpm, and the temperature was 30°C. A mixture of acrylamide, N,N-methylenebisacrylamide, ammonium persulfate and deionized water was added dropwise with stirring. The mixture was then heated to 60°C, reacted for 2 hours, and filtered to obtain polyacrylamide microspheres. The polyacrylamide microspheres, N,N-diisopropylethylamine and dichloromethane were mixed. Maleic anhydride and 1-hydroxybenzotriazole were added with stirring at a stirring rate of 200 rpm and a temperature of 0°C. The mixture was heated to room temperature and reacted for 24 hours to obtain grafted microspheres. The usage ratio of sorbitan laurate, cyclohexane, acrylamide, N,N-methylenebisacrylamide and ammonium persulfate is 1.5 g:150 mL:0.05 mol:0.05 g:0.08 g, and the usage ratio of polyacrylamide microspheres, N,N-diisopropylethylamine, maleic anhydride and 1-hydroxybenzotriazole is 6 g:0.5 mL:4 g:0.2 g; Step B2: 3-mercaptopropionic acid, 1,2-phenylenediamine and hydrochloric acid solution were mixed, and the mixture was stirred at 180 rpm and 100° C. under argon protection for 48 hours to obtain intermediate a. Intermediate a, grafted microspheres, ethanol and water were mixed, and the mixture was stirred at 300 rpm and 60° C. for 8 hours to obtain modified microspheres. The molar concentration of the hydrochloric acid solution is 4 mol / L, the amount ratio of 3-mercaptopropionic acid, 1,2-phenylenediamine and hydrochloric acid solution is 0.5 mol:0.5 mol:30 mL, and the amount ratio of intermediate a and grafted microspheres is 0.05 mol:6 g; Step B3: mixing the modified microspheres, silver nitrate solution, and ethanol, stirring at a rate of 300 rpm at room temperature for 12 hours, and filtering to obtain antibacterial water-absorbing microspheres; The mass concentration of the silver nitrate solution is 0.3 mol / L, and the dosage ratio of the modified microspheres to the silver nitrate solution is 1 g:30 mL. Example 2
[0008] A chenille waterproof mat is made by the following steps: Step S1: mixing antibacterial water-absorbing microspheres, commercially available Mingtu Chemical 2000 molecular weight polyacrylic acid, and water to prepare a microsphere finishing solution, wherein the mass concentration of the antibacterial water-absorbing microspheres in the microsphere finishing solution is 8 g / L and the mass concentration of the polyacrylic acid is 10 g / L, and finishing is performed on a commercially available Juntong polyester base fabric using a two-immersion and two-rolling method, wherein the polyester base fabric is immersed in the microsphere finishing solution, the two immersion temperatures are 40° C., the immersion time is 1 h, the bath ratio is 1:15, the roll-off rate is 80%, and then pre-baking is performed at 80° C. for 3 min and baking is performed at 120° C. for 3 min to obtain a modified base fabric; Step S2: adding the modified polyester to a melt spinning machine, melt spinning, and producing modified polyester filaments, which are then passed through a chenille spinning machine, using two commercially available Yongxing polyester yarns as core yarns and six modified polyester filaments as decorative yarns, sandwiching the decorative yarns between the two core yarns and twisting them in a spiral shape to produce modified chenille yarn; Step S3: feeding the modified chenille yarn and the modified base fabric into a tufting loom, and then dyeing, finishing, repairing, and backing the chenille yarn to produce a waterproof chenille mat; The modified polyester is prepared by the following steps: Step A1: N-methyl-4-piperidone, phenol, and deionized water were mixed, stirred at a rate of 350 rpm and a temperature of 5°C under nitrogen protection, and concentrated sulfuric acid was added dropwise, and the reaction was carried out for 48 hours to obtain intermediate 1. Intermediate 1, ethylene carbonate, potassium carbonate, and N,N-dimethylformamide were mixed, and the reaction was carried out under nitrogen protection at a rate of 350 rpm and a temperature of 160°C for 2 hours to obtain intermediate 2; The ratio of N-methyl-4-piperidone, phenol and concentrated sulfuric acid is 0.5 mol:1 mol:20 mL, and the ratio of intermediate 1, ethylene carbonate and potassium carbonate is 0.5 mol:1 mol:4 g; Step A2: Intermediate 2, dimethyl terephthalate, and ethylene glycol were mixed, stirred at a stirring rate of 400 rpm and a temperature of 200°C, and zinc acetate and antimony trioxide were added. The mixture was reacted for 1 hour, and then the temperature was raised to 250°C while controlling the vacuum degree to -0.099 MPa and the reaction was continued for 6 hours to obtain a block polyester. The ratio of intermediate 2, dimethyl terephthalate, ethylene glycol, zinc acetate and antimony trioxide is 0.05 mol: 0.1 mol: 0.35 mol: 0.05 g: 0.05 g; Step A3: The block polyester, N,N-dimethylformamide and chloroform were mixed, stirred at a stirring rate of 300 rpm and a temperature of 60° C., and propane sultone was added, and the mixture was reacted for 48 hours to obtain a modified polyester; The ratio of block polyester to propane sultone was 5 g:0.01 mol; The antibacterial water-absorbing microspheres are prepared by the following steps: Step B1: Sorbitan laurate and cyclohexane were mixed and ultrasonically dispersed for 10 minutes. Under nitrogen protection, the stirring rate was 180 rpm, and the temperature was 30°C. A mixture of acrylamide, N,N-methylenebisacrylamide, ammonium persulfate and deionized water was added dropwise with stirring. The mixture was then heated to 60°C, reacted for 2 hours, and filtered to obtain polyacrylamide microspheres. The polyacrylamide microspheres, N,N-diisopropylethylamine and dichloromethane were mixed. Maleic anhydride and 1-hydroxybenzotriazole were added with stirring at a stirring rate of 300 rpm and a temperature of 0°C. The mixture was heated to room temperature and reacted for 24 hours to obtain grafted microspheres. The usage ratio of sorbitan laurate, cyclohexane, acrylamide, N,N-methylenebisacrylamide and ammonium persulfate is 2 g:150 mL:0.05 mol:0.05 g:0.08 g, and the usage ratio of polyacrylamide microspheres, N,N-diisopropylethylamine, maleic anhydride and 1-hydroxybenzotriazole is 6 g:0.5 mL:5 g:0.2 g; Step B2: 3-mercaptopropionic acid, 1,2-phenylenediamine and hydrochloric acid solution were mixed, and the mixture was stirred at 240 rpm and 100° C. under argon protection for 48 hours to obtain intermediate a. Intermediate a, grafted microspheres, ethanol and water were mixed, and the mixture was stirred at 400 rpm and 60° C. for 8-10 hours to obtain modified microspheres. The molar concentration of the hydrochloric acid solution is 4 mol / L, the amount ratio of 3-mercaptopropionic acid, 1,2-phenylenediamine and hydrochloric acid solution is 0.5 mol:0.5 mol:40 mL, and the amount ratio of intermediate a and grafted microspheres is 0.05 mol:6 g; Step B3: mixing the modified microspheres, silver nitrate solution, and ethanol, stirring at a rate of 400 rpm at room temperature for 12 hours, and filtering to obtain antibacterial water-absorbing microspheres; The mass concentration of the silver nitrate solution is 0.3 mol / L, and the dosage ratio of the modified microspheres to the silver nitrate solution is 2 g:30 mL. Example 3
[0009] A chenille waterproof mat is made by the following steps: Step S1: mixing antibacterial water-absorbing microspheres, commercially available Mingtu Chemical 2000 molecular weight polyacrylic acid, and water to prepare a microsphere finishing solution, wherein the mass concentration of the antibacterial water-absorbing microspheres in the microsphere finishing solution is 10 g / L, and the mass concentration of the polyacrylic acid is 10 g / L. A two-immersion and two-rolling method is used to finish a commercially available Juntong polyester base fabric, wherein the polyester base fabric is immersed in the microsphere finishing solution, the two immersion temperatures are 40° C., the immersion time is 1 h, the bath ratio is 1:15, the roll-off rate is 80%, and then pre-baking is performed at 80° C. for 3 min and baking is performed at 120° C. for 3 min to obtain a modified base fabric; Step S2: adding the modified polyester to a melt spinning machine, melt spinning, and producing modified polyester filaments, which are then passed through a chenille spinning machine, using two commercially available Yongxing polyester yarns as core yarns and six modified polyester filaments as decorative yarns, sandwiching the decorative yarns between the two core yarns and twisting them in a spiral shape to produce modified chenille yarn; Step S3: feeding the modified chenille yarn and the modified base fabric into a tufting loom, and then dyeing, finishing, repairing, and backing the chenille yarn to produce a waterproof chenille mat; The modified polyester is prepared by the following steps: Step A1: N-methyl-4-piperidone, phenol and deionized water are mixed, stirred at a rate of 350 rpm and a temperature of 5° C. under nitrogen protection, concentrated sulfuric acid is added dropwise, and the mixture is reacted for 48 hours to obtain intermediate 1; intermediate 1, ethylene carbonate, potassium carbonate and N,N-dimethylformamide are mixed, and the mixture is reacted at a rate of 300-350 rpm and a temperature of 160° C. under nitrogen protection for 2 hours to obtain intermediate 2; The ratio of N-methyl-4-piperidone, phenol and concentrated sulfuric acid is 0.5 mol:1.2 mol:20 mL, and the ratio of intermediate 1, ethylene carbonate and potassium carbonate is 0.5 mol:1.2 mol:4 g; Step A2: Intermediate 2, dimethyl terephthalate, and ethylene glycol were mixed, stirred at a stirring rate of 400 rpm and a temperature of 200°C, and zinc acetate and antimony trioxide were added. The mixture was reacted for 1 hour, and then the temperature was raised to 250°C while controlling the vacuum degree to -0.099 MPa and the reaction was continued for 8 hours to obtain a block polyester. The ratio of intermediate 2, dimethyl terephthalate, ethylene glycol, zinc acetate and antimony trioxide is 0.05 mol: 0.1 mol: 0.35 mol: 0.08 g: 0.05 g; Step A3: The block polyester, N,N-dimethylformamide and chloroform were mixed, stirred at a stirring rate of 300 rpm and a temperature of 60° C., and propane sultone was added, and the mixture was reacted for 48 hours to obtain a modified polyester; The ratio of block polyester to propane sultone was 6 g:0.01 mol; The antibacterial water-absorbing microspheres are prepared by the following steps: Step B1: Sorbitan laurate and cyclohexane were mixed and ultrasonically dispersed for 10 minutes. Under nitrogen protection, the stirring rate was 180 rpm, and the temperature was 30°C. A mixture of acrylamide, N,N-methylenebisacrylamide, ammonium persulfate and deionized water was added dropwise with stirring. The mixture was then heated to 60°C, reacted for 3 hours, and filtered to obtain polyacrylamide microspheres. The polyacrylamide microspheres, N,N-diisopropylethylamine and dichloromethane were mixed. Maleic anhydride and 1-hydroxybenzotriazole were added with stirring at a stirring rate of 300 rpm and a temperature of 0°C. The mixture was heated to room temperature and reacted for 24 hours to obtain grafted microspheres. The usage ratio of sorbitan laurate, cyclohexane, acrylamide, N,N-methylenebisacrylamide and ammonium persulfate is 2 g:150 mL:0.08 mol:0.05 g:0.1 g, and the usage ratio of polyacrylamide microspheres, N,N-diisopropylethylamine, maleic anhydride and 1-hydroxybenzotriazole is 8 g:0.5 mL:5 g:0.2 g; Step B2: 3-mercaptopropionic acid, 1,2-phenylenediamine and hydrochloric acid solution were mixed, and the mixture was stirred at 240 rpm and 100° C. under argon protection for 48 hours to obtain intermediate a. Intermediate a, grafted microspheres, ethanol and water were mixed, and the mixture was stirred at 400 rpm and 60° C. for 10 hours to obtain modified microspheres. The molar concentration of the hydrochloric acid solution is 4 mol / L, the amount ratio of 3-mercaptopropionic acid, 1,2-phenylenediamine and hydrochloric acid solution is 0.6 mol:0.5 mol:40 mL, and the amount ratio of intermediate a and grafted microspheres is 0.05 mol:8 g; Step B3: mixing the modified microspheres, silver nitrate solution, and ethanol, stirring at a rate of 400 rpm at room temperature for 12 hours, and filtering to obtain antibacterial water-absorbing microspheres; The mass concentration of the silver nitrate solution is 0.3 mol / L, and the dosage ratio of the modified microspheres to the silver nitrate solution is 2 g:30 mL.
[0010] Comparative Example 1 This comparative example is compared with Example 3, except that the modified polyester in Example 3 is replaced by the block polyester in Example 3, and the other steps are the same.
[0011] Comparative Example 2 Compared with Example 3, this comparative example is different in that the modified polyester filament in Example 3 is replaced with commercially available Yongxing polyester filament, and the other steps are the same.
[0012] Comparative Example 3 Compared with Example 3, this comparative example is different in that the antibacterial water-absorbing microspheres in Example 3 are replaced by the modified microspheres in Example 3, and the other steps are the same.
[0013] Comparative Example 4 Compared with Example 3, this comparative example removes the antibacterial water-absorbing microspheres during the preparation of the modified base fabric in Example 3, and the other steps are the same.
[0014] Take a chenille waterproof mat prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, cut the chenille waterproof mat into 10 cm × 10 cm samples and weigh the dry weight, and ensure that the number of chenille piles in each sample is the same, completely soak it in water at room temperature, soak it for 3 hours, take it out and hang it until no water drops fall, weigh the wet weight, and calculate its water absorption rate as (wet weight - dry weight) / dry weight × 100% to evaluate the water absorption capacity of the chenille waterproof mat, add bovine serum albumin to a Tris-HCl buffer solution with a pH of 8 to prepare a bovine serum albumin solution, and the mass concentration of the bovine serum albumin solution is The adsorption capacity of bovine serum albumin was 1g / L. The sample was immersed in bovine serum albumin solution at room temperature for 24 hours. The sample was taken out and the protein concentration in the bovine serum albumin solution before and after immersion was measured by ultraviolet spectrophotometer at a wavelength of 280nm. The adsorption capacity of bovine serum albumin was calculated to evaluate the antifouling ability of chenille waterproof floor mats. With reference to FZ / T73023-2006, the chenille waterproof floor mats were cut into 2.5cm×2.5cm sample pieces, and the number of chenille piles in each sample piece was ensured to be the same. The antibacterial properties were determined using the oscillation method. The test bacteria were Gram-positive bacteria, Staphylococcus aureus and Gram-negative bacteria Escherichia coli. The test results are as follows: Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Water absorption rate (%) 137 141 145 132 128 138 82 <![CDATA[Adsorption amount of bovine serum albumin (mg / m 2 )]]> 72 69 71 198 207 73 69 Antibacterial rate against Gram-positive bacteria (%) 94.6 95.8 96.4 84.7 83.2 46.7 53.4 Antibacterial rate against Staphylococcus aureus (%) 94.0 94.5 95.7 82.1 80.3 45.2 54.8 Antibacterial rate against Gram-negative Escherichia coli (%) 87.7 89.2 89.3 73.4 71.6 37.9 48.7 It can be seen from the test results in the table that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, Comparative Example 1 replaces the modified polyester in Example 3 with the block polyester in Example 3. Due to the lack of zwitterionic structure in the block polyester, the prepared chenille yarn does not have hydrophilic anti-fouling properties, resulting in a decrease in its water absorption rate and a significant increase in the adsorption amount of bovine serum albumin, indicating that modified polyester can improve the water absorption and anti-fouling properties of chenille waterproof mats. Comparative Example 2 replaces the modified polyester filament in Example 3 with commercially available Yongxing polyester. Compared with Example 3, the antibacterial properties of the chenille waterproof mat are significantly reduced in Comparative Example 3, as both Comparative Example 1 and Comparative Example 2 lack quaternary ammonium groups. Compared with Example 3, the antibacterial water-absorbing microspheres in Example 3 are replaced by the modified microspheres in Example 3. Due to the lack of complex silver in the base fabric, the antibacterial properties of the chenille waterproof mat are seriously reduced. Compared with Example 3, the antibacterial water-absorbing microspheres in Example 3 are removed during the preparation of the modified base fabric. The water absorption rate and antibacterial properties of the chenille waterproof mat are significantly reduced in Comparative Example 4, indicating that the presence of the antibacterial modified microspheres can better improve the water absorption and antibacterial properties of the chenille waterproof mat.
[0015] Throughout the specification, references to terms such as "one embodiment," "example," or "specific example" indicate that the specific features, structures, materials, or characteristics described in conjunction with that embodiment or example are included in at least one embodiment or example of the present invention. In this specification, schematic representations of these terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.
[0016] The above content is merely an example and explanation of the concept of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the scope of protection of the present invention.
Claims
1. A production process for a chenille waterproof floor mat, characterized in that: The method is prepared by the following steps: Step S1: mixing antibacterial water-absorbing microspheres, polyacrylic acid and deionized water to prepare a microsphere finishing liquid, wherein the mass concentration of the antibacterial water-absorbing microspheres in the microsphere finishing liquid is 5-10 g / L, and the mass concentration of the polyacrylic acid is 10 g / L; finishing the polyester base fabric by a two-immersion and two-rolling method; the polyester base fabric is immersed in the microsphere finishing liquid; the temperature of the two immersions is 40° C., the immersion time is 1 h, the bath ratio is 1:15, the rolling rate is 80%, and then pre-baking at 80° C. for 3 min and baking at 120° C. for 3 min to obtain a modified base fabric; Step S2: adding the modified polyester to a melt spinning machine, melt spinning, and obtaining modified polyester filaments, and passing through a chenille spinning machine, using two polyester filaments as core yarns and six modified polyester filaments as decorative yarns, and sandwiching the decorative yarns between the two core yarns and twisting them in a spiral shape to obtain modified chenille yarns; Step S3: feeding the modified chenille yarn and the modified base fabric into a tufting loom, and then dyeing, finishing, repairing, and backing to obtain a chenille waterproof floor mat.
2. The production process of a chenille waterproof floor mat according to claim 1, characterized in that: The modified polyester is prepared by the following steps: Step A1: N-methyl-4-piperidone, phenol and deionized water were mixed, and concentrated sulfuric acid was added dropwise under nitrogen protection at a stirring rate of 300-350 rpm and a temperature of 5°C, and the mixture was stirred for 48 hours to obtain intermediate 1. Intermediate 1, ethylene carbonate, potassium carbonate and N,N-dimethylformamide were mixed, and the mixture was stirred at a stirring rate of 300-350 rpm and a temperature of 160°C for 2 hours under nitrogen protection to obtain intermediate 2; Step A2: Intermediate 2, dimethyl terephthalate and ethylene glycol are mixed, and zinc acetate and antimony trioxide are added under stirring conditions of 300-400 rpm and 200° C., and the mixture is reacted for 2 h, and then the temperature is raised to 250° C. and the vacuum degree is controlled to be -0.099 MPa, and the mixture is reacted for 6-8 h to obtain a block polyester; Step A3: block polyester, N,N-dimethylformamide and chloroform were mixed, stirred at a stirring rate of 200-300 rpm and a temperature of 60° C., propane sultone was added, and the mixture was reacted for 48 hours to obtain a modified polyester.
3. The production process of a chenille waterproof floor mat according to claim 2, characterized in that: In step A1: the ratio of N-methyl-4-piperidone, phenol and concentrated sulfuric acid is 0.5 mol: 1-1.2 mol: 20 mL, and the ratio of intermediate 1, ethylene carbonate and potassium carbonate is 0.5 mol: 1-1.2 mol: 4 g.
4. The production process of a chenille waterproof floor mat according to claim 2, characterized in that: The usage ratio of intermediate 2, dimethyl terephthalate, ethylene glycol, zinc acetate and antimony trioxide is 0.05 mol: 0.1 mol: 0.32-0.35 mol: 0.05-0.08 g: 0.03-0.05 g.
5. The production process of a chenille waterproof floor mat according to claim 2, characterized in that: In step A3: the ratio of block polyester to propane sultone is 4-6 g:0.01 mol.
6. The production process of a chenille waterproof floor mat according to claim 1, characterized in that: The antibacterial water-absorbing microspheres are prepared by the following steps: Step B1: Mix sorbitan laurate and cyclohexane and ultrasonically disperse for 10 minutes, stir and drop a mixture of acrylamide, N,N-methylenebisacrylamide, ammonium persulfate and deionized water under nitrogen protection, stirring at a rate of 120-180 rpm and a temperature of 30°C, then heat to 60°C, react for 2-3 hours, filter to obtain polyacrylamide microspheres, mix polyacrylamide microspheres, N,N-diisopropylethylamine and dichloromethane, stir and add maleic anhydride and 1-hydroxybenzotriazole at a stirring rate of 200-300 rpm and a temperature of 0°C, heat to room temperature, and react for 24 hours to obtain grafted microspheres; Step B2: 3-mercaptopropionic acid, 1,2-phenylenediamine and hydrochloric acid solution are mixed, and the mixture is reacted for 48 hours under argon protection, at a stirring rate of 180-240 rpm and a temperature of 100° C. to obtain intermediate a; intermediate a, grafted microspheres, ethanol and water are mixed, and the mixture is reacted for 8-10 hours at a stirring rate of 300-400 rpm and a temperature of 60° C. to obtain modified microspheres; Step B3: The modified microspheres, silver nitrate solution and ethanol were mixed, stirred at a rate of 300-400 rpm, reacted for 12 hours at room temperature, and filtered to obtain antibacterial water-absorbing microspheres.
7. The production process of the chenille waterproof floor mat according to claim 6, characterized in that: In step B1, the usage ratio of sorbitan laurate, cyclohexane, acrylamide, N,N-methylenebisacrylamide and ammonium persulfate is 1.5-2g:150mL:0.05-0.08mol:0.05g:0.08-0.1g, and the usage ratio of polyacrylamide microspheres, N,N-diisopropylethylamine, maleic anhydride and 1-hydroxybenzotriazole is 6-8g:0.5mL:4-5g:0.2g.
8. The production process of a chenille waterproof floor mat according to claim 6, characterized in that: In step B2: the molar concentration of the hydrochloric acid solution is 4 mol / L, the amount ratio of 3-mercaptopropionic acid, 1,2-phenylenediamine and hydrochloric acid solution is 0.5-0.6 mol: 0.5 mol: 30-40 mL, and the amount ratio of intermediate a and grafted microspheres is 0.05 mol: 6-8 g.
9. The production process of a chenille waterproof floor mat according to claim 6, characterized in that: In step B3: the mass concentration of the silver nitrate solution is 0.3 mol / L, and the amount ratio of the modified microspheres to the silver nitrate solution is 1-2 g: 30 mL.
10. A chenille waterproof floor mat, characterized in that: Prepared according to any one of the production processes described in claims 1-9.
Citation Information
Patent Citations
Antibacterial temperature-locking composite yarn for knitting
CN116815493A
Antiskid chenille ground mat and production process thereof
CN117845612A
Base material improved in surface characteristic
JP1996048735A
Hydrophilic finish for textiles
US6046120A
Chenille yarn for high speed weaving applications and improved product wear performance
US6107218A
Cited By
High-water-absorption chenille floor mat and production process thereof
CN119615608A
A highly absorbent chenille doormat and its production process
CN119615608B